2003
DOI: 10.2337/diacare.26.6.1719
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Meal Plan Emphasizing Healthy Food Choices Is as Effective as an Exchange-Based Meal Plan for Urban African Americans With Type 2 Diabetes

Abstract: OBJECTIVE -To compare a simple meal plan emphasizing healthy food choices with a traditional exchange-based meal plan in reducing HbA 1c levels in urban African Americans with type 2 diabetes. RESEARCH DESIGN AND METHODS -A total of 648 patients with type 2 diabeteswere randomized to receive instruction in either a healthy food choices meal plan (HFC) or an exchange-based meal plan (EXCH) to compare the impact on glycemic control, weight loss, serum lipids, and blood pressure at 6 months of follow-up. Dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 51 publications
2
50
2
6
Order By: Relevance
“…They could be used to tailor intervention and assess outcomes apart from the nutrient or food intake changes. With regards to the nutritional approaches, research evidence has shown that nutrition advice given in the form of a simple meal plan emphasizing guidelines for healthy food choices is equally effective in producing changes in glycemic control as the traditional exchange-based dietary regime [50]. Success in nutrition therapy lies in the food choices that are made.…”
Section: Conclusion: Is There Anything To Be Changed?mentioning
confidence: 99%
“…They could be used to tailor intervention and assess outcomes apart from the nutrient or food intake changes. With regards to the nutritional approaches, research evidence has shown that nutrition advice given in the form of a simple meal plan emphasizing guidelines for healthy food choices is equally effective in producing changes in glycemic control as the traditional exchange-based dietary regime [50]. Success in nutrition therapy lies in the food choices that are made.…”
Section: Conclusion: Is There Anything To Be Changed?mentioning
confidence: 99%
“…For instance, moderate caloric restriction with reduction in fat intake and increases in fruit and vegetable intake are generally accepted and effective strategies [18,19]. Controlling portion size and self-monitoring of diet and weight are also established weight management practices [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies Ziemer et al, 2003) showed significant improvements in HDL and one study reported an improvement in TG. Out of the nine studies that measured blood pressure only two studies showed significant changes as a result of the intervention Samuel Hodges, Keyserling, Park et al, 2009).…”
Section: Findings -Characteristics Of the Studiesmentioning
confidence: 99%
“…However, few studies have focused solely on how to integrate culture into dietary changes required for diabetes control (Anderson-Loftin, Barrnett, Sullivan et al, 2002; Anderson-Loftin, Ziemer et al, 2003). There is growing evidence that interventions that focus on a single health behavior, rather than multifaceted interventions (e.g.…”
Section: Complications Due To Diabetes Are Numerous and Costly Compamentioning
confidence: 99%